Challenges and opportunities of Facebook during bereavement: experiences from Taung in South Africa - Aiseng, Kealeboga (Frontiers in Communication, 2024)
Bereavement is something that we experience in one way or another. It involves many steps from one culture to the other. Many scholars have documented the role of social media tools in bereavement processes. In this study, I look at the challenges and opportunities offered by Facebook during bereavement, especially in a community that is still traditional and has yet to fully comprehend the importance of social media, particularly in matters considered sacred.The study used interviews with residents from Taung to collect data. Thematic analysis was used to analyze the collected data from the interviews. The study findings indicate some challenges associated with bereavement on Facebook: emotional shock, lack of sensitivity, misinformation, and cultural dilution. There are also opportunities: fast news sharing, ongoing emotional support, and sharing of memories. The study argues that the findings should expand our understanding and knowledge of bereavement in some African cultures and use social media tools to complement and not destroy African beliefs and practices.